Alleviating Poverty through Business Strategy - Wankel, C. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
There is a growing realization that business development is the most effective weapon in fighting world poverty. How the for-profit model can be harnessed to provide the poor with a share in the world's prosperity is discussed through actual cases, and nested in innovative theories of business, social sciences, and philosophy.